The effect of symbiotic supplementation on liver enzymes, c-reactive protein and ultrasound findings in patients with non-alcoholic fatty liver disease: A clinical trial - Atefe Asgharian (International Journal of Preventive Medicine, 2016)
Background: Regarding to the growing prevalence of nonalcoholic fatty liver disease (NAFLD), concentrating on various strategies to its prevention and management seems necessary. The aim of this study was to determine the effects of symbiotic on C-reactive protein (CRP), liver enzymes, and ultrasound findings in patients with NAFLD. Methods: Eighty NAFLD patients were enrolled in this randomized, double-blind, placebo-controlled clinical trial. Participants received symbiotic in form of a 500 mg capsule (containing seven species of probiotic bacteria and fructooligosaccharides) or a placebo capsule daily for 8 weeks. Ultrasound grading, CRP, and liver enzymes were evaluated at the baseline and the end of the study. Results: In the symbiotic group, ultrasound grade decreased significantly compared to baseline (P < 0.005) but symbiotic supplementation was not associated with changes in alanine aminotransferase (ALT) and aspartate transaminase (AST) levels. In the placebo group, there was no significant change in steatosis grade whereas ALT and AST levels were significantly increased (P = 0.002, P = 0.02, respectively). CRP values remained static in either group. Conclusions: Symbiotic supplementation improved steatosis in NAFLD patients and might be useful in the management of NAFLD or protective against its progression.